Application of nanotechnology in the treatment of hepatocellular carcinoma - Cai, Liu; Du, Yanyuan; Xiong, Hongtai; Zheng, Honggang (Frontiers in Pharmacology, 2024)
Hepatocellular carcinoma is the predominant histologic variant of hepatic malignancy and has become a major challenge to global health. The increasing incidence and mortality of hepatocellular carcinoma has created an urgent need for effective prevention, diagnosis, and treatment strategies. This is despite the impressive results of multiple treatments in the clinic. However, the unique tumor immunosuppressive microenvironment of hepatocellular carcinoma increases the difficulty of treatment and immune tolerance. In recent years, the application of nanoparticles in the treatment of hepatocellular carcinoma has brought new hope for tumor patients. Nano agents target tumor-associated fibroblasts,regulatory T cells, myeloid suppressor cells, tumor-associated macrophages, tumor-associated neutrophils, and immature dendritic cells, reversed the immunosuppressive microenvironment of hepatocellular carcinoma. In addition, he purpose of this review is to summarize the advantages of nanotechnology in guiding surgical excision, local ablation, TACE, standard chemotherapy, and immunotherapy， application of nano-vaccines has also continuously enriched the treatment of liver cancer.This study aims to investigate the potential applications of nanotechnology in the management of hepatocellular carcinoma, with the ultimate goal of enhancing therapeutic outcomes and improving the prognosis for patients affected by this malignancy.